Incorporação imobiliária como efetivação do direito à moradia digna: rescisão contratual pelo consumidor na perspectiva da Lei n. 13.786/ 2018 - Oliveira, Andrea Silvana Fernandes de (2019)
The real estate development is the activity carried out with the purpose of promoting the construction and obtaining of the necessary capital for the construction of the enterprise, being realized through the advance sale of the autonomous units, constructed with the amount collected of sales, or of a bank financing , regulated by Law No. 4,591 / 1964. Allied to an economic vision, it is pointed out as a possibility to make the right to housing feasible (constitutional plan), without involving large-scale public resources (economic plan). This activity is carried out through the preliminary contract for the purchase and sale of properties subject to the Consumer Protection Code when it characterizes consumer relations, resulting in a dialogue of sources between the rules of Law 4591/1964 and Civil Code of 2002, to regulate judicial impasses. With the severe economic crisis in Brazil, the number of distractions aimed at extinguishing the obligations established in a previous contract, which has not yet been fully implemented, increased. In order to avoid any abusive contractual clause regarding the return of amounts paid, the Superior Court of Justice issued a summary 543, establishing how the court decision should be in case of contractual termination of the purchase of real estate, in order to protect the acquirer / consumer. With the purpose of regulating the distract, came the Law of Distract - Law nº 13.786, which deals with aspects involving the resolution and resilience of real estate sales contracts under real estate development or subdivision. Thus, the real estate sector has a high importance for the economic growth of Brazil, the present research has as general objective to analyze the economic and financial effects of the distract in the real estate development contracts made by the promising buyer, falling into consumer protection standards, observing principles of equilibrium contractual obligations of the parties and social justice. The methodology to be used for the collection and absorption of information consists of research in the various sources of law, especially legislation, doctrine and jurisprudence, associated with legal reflection on the subject, with the scope of demonstrating the objectives to be achieved.